Corrigendum: Computer based body exposure in adolescents with anorexia nervosa: a study protocol (Frontiers in Psychiatry, (2022), 12, (769239), 10.3389/fpsyt.2021.769239) - Stonawski, Valeska; Sasse, Lena; Moll, Gunther; Kratz, Oliver; Horndasch, Stefanie (Frontiers in Psychiatry, 2025)
In the published article, an Acknowledgments section was mistakenly not included in the publication. This section has now been added: “Acknowledgments This paper is part of the fulfillment of obtaining a doctoral degree for Lena Sasse.” The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.
CRIS-Team Scopus Importer:2025-05-16
Keywords: adolescence; anorexia nervosa; attentional bias; body dissatisfaction; body exposure; eye tracking; randomized controlled trial (RCT); stress reactivity